Penerapan e-Government di Merauke: Studi Kasus Sistem Pelayanan Publik Berbasis Teknologi Informasi - Enala, Syahrabudin Husein; Vinsenco R. Serano (Papsel Journal of Humanities and Policy, 2025)
This study aims to analyze the implementation of e-Government in enhancing technology-based public services in Merauke Regency. The primary focus of this research is to identify the challenges and benefits derived from implementing the e-Government system across various local government agencies. The benefit of this research lies in providing recommendations for local governments to improve efficiency, transparency, and accountability in public services through the utilization of information technology. The research problem addressed is how the implementation of e-Government in Merauke Regency can improve the quality of public services and what obstacles are encountered during its implementation. The research employs a qualitative approach with a case study design, where data is collected through interviews with local government officials, direct observations in several agencies implementing e-Government, and document analysis related to policies and system implementation. The findings indicate that while the implementation of e-Government in Merauke has improved the accessibility and efficiency of public services, several challenges remain, including inadequate technological infrastructure, limited human resource capacity, and low levels of digital literacy among the population. However, positive outcomes were also noted, such as the reduction of bureaucracy, acceleration of service processes, and increased transparency in public administration management. This study recommends that the Merauke government strengthen technological infrastructure, provide continuous training for government officials, and raise public awareness regarding the importance of utilizing digital systems. Keywords: e-Government, public services, information technology